Cultivation of Folia digitalis - Raina, V. (Indian Forester, 1959)
Folia digitalis (Syn. Digitalis purpurea) is a medicinal plant of high value. It is not indigenous to India but it is cultivated in temperate hill stations. Complete details regarding its cultivation are furnished, concerning such items as nursery practice, method of planting, manuring, harvesting, storage of leaves, etc. The leaves of plants raised at Lachog in Solan Division were analysed, and found to have a potency equivalent of 31.5 units per gram or 252% stronger than the international digitalis powder. The yield of leaves varied from 500 to 1,000 pounds per acre.